Legal Construction of the Fatwas of the Tarjih and Tajdid Councils Muhammadiyah Regarding Family Law - Mustakim, Rizki; Sanusi, Muhammad Fahmi; Sukendar, Rita; Kumbara, Ruhiyat; Abdillah, Tresna Mugni; Jamarudin, Ade (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstracts: At the beginning of the 20th century, Islamic organizations such as Muhammadiyah, Naahdhatul Ulama and others were born, which of course were very concerned with Islamic law. Each organization has a special council in charge of religious fatwas which are practically a guide in everyday life. Family Law is an interesting part of community practice for discussion, among which are the fatwas of the Tarjih Council and the Tajdid Muhammadiyah. The assembly in charge of religious fatwas has a progressive view in several family law cases, such as unregistered marriages or marriages under the hand. This assembly is of the view that marriages that are not registered at state institutions are invalid. Religious texts (bayani) are prioritized in this fatwa and are supported by social science (burhani), and place marriage as a sacred contract ('irfani) which needs to be institutionalized according to legal certainty in order to maintain maqashid al-shari'ah which is fostered by five things: guarding religion, soul, mind, lineage, and wealth Keywords: Legal Construction, Fatwa, Tajdid Muhammadiyah, Family Law Abstrak: Di awal abad XX lahir organisasi-organisasi Islam seperti Muhammadiyah, Naahdhatul Ulama dan lain-lainya yang tentu saja sangat konsen dengan Hukum Islam. Setiap organisasi memiliki majelis khusus yang membidangi tetang fatwa-fatwa keagamaan yang secara praktis menjadi tuntunan dalam kehidupan sehari-hari. Hukum Keluarga adalah bagian dari pengamalan masyarakat yang menarik untuk didiskusikan, di antaranya adalah fatwa-fatwa Majelis Tarjih dan Tajdid Muhammadiyah. Majelis yang membidangi fatwa keagamaan ini memiliki pandangan yang progresif dalam beberapa kasus hukum keluarga, seperti nikah sirri atau nikah di bawah tangan. Majelis ini berpandangan bahwa nikah yang tidak dicatatkan di lembaga negara adalah tidak sah. Nash-nash agama (bayani) menjadi prioritas dalam fatwa ini dan didukung dengan ilmu pengetahuan sosial kemasyarakatan (burhani), serta menempatkan pernikahan sebagai akad sakral (‘irfani) yang perlu dilembagakan sesuai kepastian hukum demi menjaga maqashid al-syari’ah yang dibina atas lima hal: menjaga agama, jiwa, akal, keturunan, dan harta.Kata Kunci : Fatwa, Tajdid Muhammadiyah, Hukum Keluarga